FRI0395 Effect of Rituximab on Different Isotypes of Serum Immunoglobulins in Patients with Sle. (10th June 2014) - Reddy, V.; Martinez, L.; Isenberg, D.; Cambridge, G.; Leandro, M.
Abstract : Background: The impact of rituximab therapy on different compartments of the immune system may inform as to the possible clinical response and also maintenance of protective immunity. We conducted a retrospective study of serum IgM, IgG and IgA in 57 patients with SLE, following the first cycle of B cell depletion therapy based on rituximab (RTX). Methods: Serum Ig levels (IgA, IgG and IgM) were assessed at baseline (before first infusion of RTX) and at 1, 2, 6, 9 and 12 months after the first cycle of RTX in 57 patients with SLE. Paired t-test and Spearman's rank correlation were used to analyse changes in serum Ig levels and to analyse correlations, respectively. Results: Median baseline serum IgA level was 2.9g/L, which fell by a mean 6% and 10% (p<0.05), at 1 and 2 months after RTX but was similar to baseline at 12 months. IgA levels at baseline showed a positive correlation with IgA levels at all time points (r 2 ≥0.5, p<0.0001 for all). Median baseline serum IgG level was 13.9g/L, which was significantly reduced (p<0.05) (means of 7%, 11%, 5% and 7% at 1, 2, 6, and 9 after RTX) but levels were similar to baseline at 12 months. Median baseline serum IgM levels were 1.0g/L, which reduced by means of 13%, 18%, 17%, 29% and 18% at 1, 2, 6, 9, and 12 months respectively (p<0.005 for all). Serum IgG levels at 12 months either reduced (group1) or increased (group2) from baseline. Interestingly, there was a significant difference in baseline IgG levels between the two groups with a median level of 17.24g/l and 10.7g/l (p=0.0005) for group 1 and 2, respectively. Baseline IgG levels positively correlated with IgG levels at all time-points (r 2 ≥0.6, p<0.005 for all). However, there was no difference in IgG levels at 12 months between the two groups. There was a significant difference in baseline IgM levels between the group of patients who had IgM levels <0.4 at 12 months and those who did not, median levels of 0.48 and 1.05g/l, respectively. There was no correlation between absolute numbers of CD19+cells at baseline and serum Ig levels or %change in Ig levels at any time-points. Conclusions: Our results reveal a disparity in changes in IgA, IgG and IgM levels following rituximab treatment in SLE. Disease-associated defects in B cell biology particularly accessory cell and T-cell interactions associated with B cell survival and class-switch may, at least in part, account for this disparity. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4559